Anetso, the Cherokee Ball Game : At the Center of Ceremony and Identity - Zogry, Michael J., 1966- (Book collections on Project MUSE., 2010)
A precursor to lacrosse, anetso, a centuries-old Cherokee ball game still played today, is a vigorous sport that rewards speed, strength, and agility. It is also the focus of several linked ritual activities. Zogry argues that members of the Eastern Band of Cherokee Nation continue to perform selected aspects of their cultural identity by engaging in anetso. He shows that it is a ceremonial cycle that incorporates a variety of activities which, taken together, complicate standard distinctions of game versus ritual, public display versus private performance, and tradition versus innovation.